Zinco e manganês orgânicos e vitamina d3 em rações de poedeiras com idade avançada - Santos, Edibergue Oliveira dos (2017)
The production of commercial eggs presents limitations with the advancing age of laying hens, caused by the increase of egg losses due to the poor quality of the eggshell. The objective of this study was to evaluate the effects of supplementation with the organic microminerals zinc and manganese and vitamin D3 in the diets of laying hens from 86 to 100 weeks of age. In addition to evaluating these effects on performance, egg quality, lipid stability of fresh and stored eggs and bone quality. A total of 288 laying hens of the Dekalb White line were distributed in a completely randomized design with 6 treatments of 6 replicates of 8 hens each, in which they were tested: a control diet and other five diets with the supplements of zinc; manganese, zinc and manganese, vitamin D3, zinc, manganese and vitamin D3. In the performance, there was no significant interaction between the treatments and the evaluation period for any of the variables, but there was a significant difference in feed intake, with lower values for the Laying hens supplemented with organic manganese showed the lowest result. It was also observed a significant difference between the periods for all variables, except for egg weight. In the evaluation of egg quality there was no significant interaction between diet and the evaluation period for any of the variables. However, the diet offered to laying hens significantly influenced the egg shell thickness, being observed that the supplementation with organic zinc and manganese, with vitamin D3 alone or with organic zinc and manganese and vitamin D3 resulted in higher thickness than eggs from the birds that received control diet, with no difference for the other variables. The evaluation of the lipid stability of the yolk, measured by the Tbars values, showed that there was no significant interaction between the diets and storage time. It was also observed that the different supplements did not significantly influence the lipid stability of the egg yolk. However, lipid stability varied according to storage time, with increase of Tbars values with storage prolongation up to 28 days. The different dietary supplements did not influence any of the bone quality variables measured in the tibia and femur of the laying hens. The supplementation, associated or isolated, of organic zinc and manganese microminerals and of vitamin D3 (25-OHD3) in the diet of laying hens of old age not influence the performance, lipid stability of fresh and stored egg yolk and bone quality; but supplementation of zinc and manganese alone, vitamin D3 alone, or the combination of these two organic minerals with vitamin D3 improve the egg shell thickness.